Ibadah Mengolah Sampah Di Desa Grobog Wetan Kecamatan Pangkah Kabupaten Tegal - Mubarok, Zaki; Koidin, Mohammad (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2020)
Having religion actually makes religious doctrine as an energy in solving the problems of humanity, one of them is the waste problem. The religious doctrine of the perfection of faith obtained by maintaining cleanliness must be realized by cooperating with multiple disciplines or other entities as an effort to create a clean and healthy society. The paradox of the society which is being busy with religious rituals, but neglecting the cleanliness of the environment continues until today, including in Grobog Wetan Village, Pangkah District, Tegal Regency. Initially this dedications was planned with the Almaghfiroh Foundation. However, in its development also with the Village Government, Youths, Fatayat, RT, RW and Nature Lovers Students.This dedication in dealing with the problem of garbage aims to bring up a paradigm of dealing with waste problems as a worshipping ritual, getting reward as in other rituals. It also makes waste as something which is close and can be treated as something economical. By using the society intervention method, the result of this service is a process in which the society developing a pattern of sorting and processing organic and inorganic waste. Organic waste is transformed into magot caterpillar food and inorganic waste is still in the process of being transformed into tradable goods. In addition, the fundamental achievement of this research-based dedication is the emergence of a new understanding for the society not to "hostile" waste, but to be close to the waste, which exists a daily life and eventually to "make friends" with waste. This service also recommends the village government to create a waste management budget on a larger scale. These achievements must also be interpreted and disseminated to the society as a form of worshipping.Beragama sejatinya menjadikan doktrin agama sebagai energy dalam memecahkan masalah kemanusiaan, salah satunya masalah sampah. Doktrin agama tentang kesempurnaan iman diperoleh dengan menjaga kebersihan harus direalisasikan dengan menggandeng berbagai disiplin atau entitas lain sebagai upaya mewujudkan masyarakat yang bersih dan sehat. Paradoks masyarakat sibuk ritual keagamaan namun abai dengan kebersihan lingkungan terus beralangsung hingga saat ini. Termasuk di Desa Grobog Wetan Kecamatan Pangkah Kabupaten Tegal. Awalnya pengabdian ini direncanakan bersama Yayasan Almaghfiroh. Namun dalam perkembangannya juga dengan Pemerintah Desa, Para Pemuda, Ibu-Ibu Fatayat, RT , RW dan Mahasiswa Pecinta Alam.Pengabdian dalam menangani masalah sampah ini bertujuan untuk memunculkan paradigma menangani masalah sampah sebagai ibadah, berpahala sebagaimana ibadah ritual lain. Juga menjadikan sampah sebagai sesuatu yang dekat dan bisa diperlakukan sebagai sesuatu yang ekonomis. Dengan menggunakan metode intervensi komunitas, hasil pengabdian ini berupa proses. Yaitu masyarakat mengembangkan pola pilah dan olah sampah organic dan an organic. Sampah organic ditransformasikan menjadi makanan ulat magot dan sampah an organic masih dalam tahap proses transformasi menjadi barang yang diperjual belikan. Selain itu, capaian mendasar dari pengabdian berbasis riset ini adalah munculnya pemahaman baru bagi masyarakat untuk tidak â€œmemusuhiâ€ sampah, melainkan dekat dengan sampah yang merupakan kenyataan dalam keseharian dan akhirnya â€œbertemanâ€ dengan sampah. Pengabdian ini juga merekomendasikan pemerintah desa untuk membuat anggaran penanganan sampah dalam skala yang lebih besar. Capaian-capaian ini pula harus dimaknai dan disemaikan kepada masyarakat sebagai bentuk ibadah.Â  Â